Uji ketahanan galur padi terhadap wereng coklat biotipe 3 melalui population build-up - Baehaki Suherlan Effendi; Dede Munawar (Jurnal Entomologi Indonesia, 2013)
Screening of rice lines resistance to brown planthopper (BPH) through mass screening, filtering line resistance and the population build-up are essential for the release of resistant rice varieties. In addition, the stages of the endurance are important in determining the stability of resistance, as well as the type of resistant. The research was carried out in the screen house at Indonesian Center for Rice Research in 2007. The BPH used in the research was the off spring of BPH biotype 3 that had been rearing on IR42 (bph2) variety since 1994. The result of this research showed that 22.2% of 18 lines/varieties were moderately resistant to BPH biotype 3ft namely BP4130-1f-13-3-2*B, BP4188-7f-1-2-2*B, BP2870-4e- Kn-22-2-1-5*B, and Pulut Lewok. On the population build-up test, the above lines/varieties were moderately resistant to BPH biotype 3pb. The low FPLI values were found in BP4130-1f-13-3-2*B and Pulut Lewok. The highest tolerance index was found on BP4130-1f- 13-3-2*B and Pulut Lewok followed by BP2870-4e-Kn-22-2-1-5*B and BP4188-7f-1-2-2*B. Pulut Lewok has the highest antibiosis index and is not significantly different to BP4130-1f-13-3-2*B, while BP4188-7f-1-2-2*B was lowest. Although Pulut Lewok has antibiosis defense mechanism, it is not tolerant to BPH biotype 3. The BP4130-1f-13-3-2*B line have both antibiosis and tolerant to BPH biotype 3. BP4188-7f-1-2-2*B line has tolerance character, but does not have character of antibiosis to BPH biotype 3.